Associations between attention‐deficit hyperactivity disorder (ADHD) symptom remission and white matter microstructure: A longitudinal analysis - Anne E. M. Leenders (Wiley, 2021)
Abstract Background Attention‐deficit hyperactivity disorder (ADHD) is associated with white matter (WM) microstructure. Our objective was to investigate how WM microstructure is longitudinally related to symptom remission in adolescents and young adults with ADHD. Methods We obtained diffusion‐weighted imaging (DWI) data from 99 participants at two time‐points (mean age baseline: 16.91 years, mean age follow‐up: 20.57 years). We used voxel‐wise Tract‐Based Spatial Statistics (TBSS) with permutation‐based inference to investigate associations of inattention (IA) and hyperactivity‐impulsivity (HI) symptom change with fractional anisotropy (FA) at baseline, follow‐up, and change between time‐points. Results Remission of combined HI and IA symptoms was significantly associated with reduced FA at follow‐up in the left superior longitudinal fasciculus and the left corticospinal tract (CST; PFWE = 0.038 and PFWE = 0.044, respectively), mainly driven by an association between HI remission and follow‐up CST FA (PFWE = 0.049). There was no significant association of combined symptom decrease with FA at baseline or with changes in FA between the two assessments. Conclusions In this longitudinal DWI study of ADHD using dimensional symptom scores, we show that greater symptom decrease is associated with lower follow‐up FA in specific WM tracts. Altered FA thus may appear to follow, rather than precede, changes in symptom remission. Our findings indicate divergent WM developmental trajectories between individuals with persistent and remittent ADHD, and support the role of prefrontal and sensorimotor tracts in the remission of ADHD.